Pengaruh Frekuensi Olahraga terhadap Indeks Massa Tubuh pada Mahasiswa dan Mahasiswi Fakultas Kedokteran Universitas YARSI Angkatan 2013 dan 2014 - Adinda Amalia Sholeha; Qomariyah Qomariyah (Lembaga Penelitian Universitas YARSI, 2018)
The frequency of exercise is one of the factors that affect body mass index(BMI). The frequency of exercise of each person is varies in a week. Thisresearch discusses the effect of frequency of exercise on BMI on thestudent of Faculty of Medicine YARSI Univeristy 2013 and 2014generations. In this research, a sample of 86 people with cross sectionalresearch methods by filling out a questionnaire and measured the heightand weight then these data are processed using Chi Square statisticaltest. From the results, the average frequency of exercise is in the mediumcategory which is 2-3 times a week. In the Chi Square statistical testobtained P value 0.272 (p more than 0.05) on the male student and P value 0649 (p more than 0.05) on the female students. It was not statistically significant relationship exists between the frequency of exercise on BMI. BMI is not only influenced by the frequency of exercise per person. There are many factors that affect that is genetic, nutritional, environmental, and disease. Additional research can be expected to do further research to include other factors that affect BMI.